PROFIL TES DARAH RUTIN DAN JUMLAH LIMFOSIT TOTAL PADA PENDERITA HIV/AIDS - Amraini Afiah; M. Arif; Hardjoeno Hardjoeno (Indonesian Association of Clinical Pathologist and Medical laboratory, 2007)
CD4 test and Viral Load have been done for initiating, controlling, and deciding the treatment and prognosis of HIV/AIDS.If bothtests cannot be done, clinical symptoms and total lymphocyte count (TLC) can be used. TLC and Hb can be used for monitoring theHIV progressiveness. To evaluate routine blood test results, TLC, and CD4 of HIV/AIDS patients. Cross sectional and descriptive studyfrom October 2005 to April 2006, of 30 patients, i.e. 21 men (70%) and 9 women (30%). Leucopenia was found in 16.67% men and13.33% women. Anemia Hb in 70% men and 30% women with mean value 2.52 g/dl; lymphocytopenia in 46.67% men and 10%women; and netropenia in 16.67% men and 10% women. CD4 was discovered decline in 66.67% men and 30% women with mean value63.4 cell/mm3. TLC in 43.33% men and 16.67% women with mean value 1081.21 cell/mm3. In the study we found i.e. leucopenia,anemia, limfocytopenia, and neutropenia. CD4 and TLC are mostly decline. Further researches in the bigger populations are conductedto consider the parameter of routine blood tests, TLC, and CD4 on HIV/AIDS patients for initiating therapy.